2005
DOI: 10.1111/j.1365-2745.2005.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory, time since introduction and the invasiveness of exotic plants

Abstract: Summary 1We tested the enemy release hypothesis for invasiveness using field surveys of herbivory on 39 exotic and 30 native plant species growing in natural areas near Ottawa, Canada, and found that exotics suffered less herbivory than natives. 2 For the 39 introduced species, we also tested relationships between herbivory, invasiveness and time since introduction to North America. Highly invasive plants had significantly less herbivory than plants ranked as less invasive. Recently arrived plants also tended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
133
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 28 publications
13
133
2
1
Order By: Relevance
“…Because the rate at which invasive species become established is increasing in many parts of the world, understanding the dynamics of invasion is critical (2,3). Transport of a species out of its native habitat is thought to result in a reduction in herbivory because of the absence of coevolved specialist insects (4,5); this reduction is postulated to divert investment of resources from chemical defense and toward increased competitive ability (5,6). Indeed, the idea that plant populations in areas of indigeneity are regulated by herbivores underlies the practice of classical biological control of weeds (7,8).…”
mentioning
confidence: 99%
“…Because the rate at which invasive species become established is increasing in many parts of the world, understanding the dynamics of invasion is critical (2,3). Transport of a species out of its native habitat is thought to result in a reduction in herbivory because of the absence of coevolved specialist insects (4,5); this reduction is postulated to divert investment of resources from chemical defense and toward increased competitive ability (5,6). Indeed, the idea that plant populations in areas of indigeneity are regulated by herbivores underlies the practice of classical biological control of weeds (7,8).…”
mentioning
confidence: 99%
“…In one of the few studies that have considered differences in the invasiveness level of exotic plants, Mitchell & Power (2003) found that greater release from fungal pathogens was correlated with greater invasiveness in 473 European plant species naturalized in the United States. Likewise, our previous work revealed a negative correlation between herbivory and invasiveness (Carpenter & Cappuccino 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, comparisons of herbivory on exotics and natives typically overlook the invasiveness status of the exotic plants. In two recent exceptions, plants that were more invasive tended to have fewer pathogens (Mitchell & Power 2003) and less leaf herbivory (Carpenter & Cappuccino 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies use the same comparison but quantify damage typically caused by predators, e.g., leaf damage (Lewis et al 2006;Ebeling et al 2008). Another approach is to compare invasive to similar or related native species, and again, in some cases infestation is quantified (Frenzel and Brandl 2003;Blakeslee and Byers 2008), in others damage (Carpenter and Cappuccino 2005;Sugiura 2010). The case is even more complicated by the fact that some comparisons analyze the importance of generalist predators (Jogesh et al 2008), others that of specialist predators (Memmott et al 2000;Liu et al 2007).…”
Section: Invasion Theory: Lack Of Synthesis and Imprecise Hypothesesmentioning
confidence: 99%